Mesenteric panniculitis patients requiring emergency surgery: Report of three cases - Mustafa DUMAN; Osman KOÇAK; Olgaç FAZLI; Cengiz KOÇAK; Ali Emre ATICI; Uğur DUMAN (Turkish Journal of Gastroenterology, 2019)
-